anonymous
  • anonymous
When you start with the function f^2(1)=2*2*1=4, if asked to repeat the process with an initial value of -1, does that mean :f^2(-1)=2*2*1 OR f^2(-1)=2*2*-1
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
I believe it is the second one.
anonymous
  • anonymous
Thank you!
anonymous
  • anonymous
i would love to know what \[ f^2(1)=2*2*1=4\] means

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
It is reasonable to assume that because f(1) is there that the 1 in the equation is the x spot for f(x).
anonymous
  • anonymous
f is either -2 or 2.
anonymous
  • anonymous
That is what I thougt. Chaos Theory project.
anonymous
  • anonymous
Probably 2. However, you can't really figure out how 2 is made because they don't give you the original function.
anonymous
  • anonymous
f(x)=2x given initial value of 1
anonymous
  • anonymous
iterations..f(1) = 2*1 = 2 , f^2(1) = 2*2*1 =4, f^3 (1) = 2*2*2*1=8. Replace initial value with -1 to find pattern.
anonymous
  • anonymous
maybe it is \[f(x)=2x\\ f(-1)=-2\\ f^2(-1)=2\times 2\times -1=-4\\ f^3(-1)=-8 ...\\ f^n(-1)=-2^n\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.